Under Sustainable Agriculture Practices: Evaluation of Imidacloprid Toxicity on Soil Organisms - Neamah, Asmaa M.; Alkadhimy, Sura M.; Ibadi, Emam Atiyah (American Journal of Biology and Natural Sciences, 2026)
Background: Microbial communities and soil organisms such as earthworms and soil organisms support sustainable farming, spearheading nutrient cycling, organic matter breakdown, and soil aeration. Earthworms increase soil porosity and water absorption, and microorganisms promote the fixation of nitrogen and carbon. Disturbances in these biota have cascades in food webs which affects the crop productivity and resistance to climate stressors such drought. Objective: In this work, the toxicological impact of these pesticides on several important soil biota is evaluated in simulated conditions of sustainable agricultural production in order to achieve soil biodiversity. Results : The use of imidacloprid as a representative neonicotinoid was based on its prevalence and persistence in the soil.No mortality was observed in earthworms or springtails exposed to imidacloprid (survival >95%). Reproduction declined significantly at concentrations ≥1 µg/kg (p < 0.01). hEisenia fetida and Folsomia candida, while the Lowest Observed Effect Concentration (LOEC) was determined at 1 µg/kg, where significant reductions in juvenile production were first observed (p < 0.01). The increasing concentration of imidacloprid is observed to affect the enzyme activities in a progressive reduction, which implies its direct inhibitory effect on the soil microbial metabolism. The activity of dehydrogenase, the measure of the general oxidative activity of the microbes, was the most sensitive to pesticide exposure and was reduced by 42% at the highest concentration (10 ug/kg). The beneficial functions that soil organisms contribute to the nutrient cycle, neonicotinoids may interfere with them by being bioaccumulated in the soil and having sublethal impacts such as lowered reproduction and hindered microbial activity. Conclusion: rotation agents, and using more precise application methods might be useful in reducing the possible ecological effects. The issue of effects of pesticide exposure over the long term and over multiple generations, and the variability of soil when subjected to field conditions should also be viewed in the future research insight into the ecological impacts of accumulation of neonicotinoids in agricultural soils.